Effect of different feeds on growth, survival and production of freshwater mud eel, Monopterus cuchia (Hamilton) - Narejo, N T; Rahmatullah, S M; Rashid, M Mamnur (Indian Journal of Fisheries, 2011)
An experiment was conducted to study the effect of different feeds on growth, survival and production of freshwater mud eel, Monopterus cuchia reared in cemented cisterns (1.25m2 each) over a period of twelve months from July 2000 to June 2001. Three different feeds namely F 1(live small fish), F 2 (dead small fish) and F 3 (pellet feed, 30% protein) were applied to treatment I, II and III respectively. Each cistern was stocked with ten fish having mean initial body weight of 30.5 ± 4.25 g, each treatment was replicated thrice. Highest weight gain of 71.20 ± 3.78 g was obtained in treatment II (p<0.05), followed by treatment I (46.46 ± 2.30 g) and lowest 26.10± 2.40 g in treatment III. Survival 76.66 ± 4.76%, specific growth rate 0.3297 ± 0.01 and production 0.624 ± 0.056 Kg/ m2/ year were also highest in treatment II. Weight gain was observed throughout the study period from February to November. However, slight weight loss (estivation) was observed during winter from December to January. Water quality parameters like temperature, dissolved oxygen, pH and alkalinity were optimum. On the basis of better growth, survival rate and production, it is suggested that dead small fish are suitable for the culture of M. cuchia in cemented cisterns